Bortezomib initiates endoplasmic reticulum stress, elicits autophagy and death in Echinococcus granulosus larval stage - Nicolao, María Celeste (PLoS One, 2017)
Cystic echinococcosis (CE) is a worldwide distributed helminthic zoonosis caused by Echinococcus granulosus. Benzimidazole derivatives are currently the only drugs for chemotherapeutic treatment of CE. However, their low efficacy and the adverse effects encourage the search for new therapeutic targets. We evaluated the in vitro efficacy of Bortezomib (Bz), a proteasome inhibitor, in the larval stage of the parasite. After 96 h, Bz showed potent deleterious effects at a concentration of 5 μM and 0.5 μM in protoscoleces and metacestodes, respectively (P < 0.05). After 48 h of exposure to this drug, it was triggered a mRNA overexpression of chaperones (Eg-grp78 and Eg-calnexin) and of Eg-ire2/Eg-xbp1 (the conserved UPR pathway branch) in protoscoleces. No changes were detected in the transcriptional expression of chaperones in Bz-treated metacestodes, thus allowing ER stress to be evident and viability to highly decrease in comparison with protoscoleces. We also found that Bz treatment activated the autophagic process in both larval forms. These facts were evidenced by the increase in the amount of transcripts of the autophagy related genes (Eg-atg6, Eg-atg8, Eg-atg12, Eg-atg16) together with the increase in Eg-Atg8-II detected by western blot and by in toto immunofluorescence labeling. It was further confirmed by direct observation of autophagic structures by electronic microscopy. Finally, in order to determine the impact of autophagy induction on Echinococcus cell viability, we evaluated the efficacy of Bz in combination with rapamycin and a synergistic cytotoxic effect on protoscolex viability was observed when both drugs were used together. In conclusion, our findings demonstrated that Bz induced endoplasmic reticulum stress, autophagy and subsequent death allowing to identify unstudied parasite-host pathways that could provide a new insight for control of parasitic diseases.